Investigating the Student’s Writing Ability by Using Dictogloss Technique at MTs Al-Jami’yatul Washliyah 40 Tinokkah - Damanik, Indra Jayanti; Ramadani, Safti Witria; Purba, Benarita; Zou, Guijiao; Jie, Lie; Jixiong, Cai (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
The aim of this research is to find out the using dictogloss technique improve the students’ writing ability of descriptive text at second grade of MTs Al-jam’iyathul washliyah 40 Tinokkah. The researcher used quantitative approch with pre-experimental research design. Population of this research was eight grade with three classes which consists of 108 students and the sample of research was 72 students in two classes. The technique of collecting data was pre-test and post-test. The technique of analysis data by using SPSS (26.0). The result of this research was obtained tcount= 9.863 > ttable= 1.689 at the significance level ?=0.05 and degrees of freedom (df) = 35, HO is rejected and H? is accepted and implies that the students taught by using dictogloss technique achieve a better score in descriptive text. It means that there are significantly on student writing ability by using dictogloss technique in English subject about descriptive text in eight grade of MTs Al-jam’iyatul Washliyah 40 Tinokkah. Overall, the researcher provides a great starting point for discussion on the use dictogloss technique to write down the sentences, discuss them in groups, and learn new vocabulary. The students helped students to double-check their work and correct.